2021
DOI: 10.3390/ani11061628
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graded Substitution of Soybean Meal by Hermetia illucens Larvae Meal on Animal Performance, Apparent Ileal Digestibility, Gut Histology and Microbial Metabolites of Broilers

Abstract: The usage of insects as an alternative protein source for broiler feeds may help to reduce the dependency on soybean meal (SBM) imports. Therefore, the present study aimed to evaluate the replacement of 15 (SL15) or 30% (SL30) of crude protein (CP) from SBM with Hermetia illucens (HI) defatted larvae meal regarding broiler performance, carcass traits, apparent ileal digestibility, intestinal morphology, and microbial metabolites. Concerning the performance, body weight was similar for the control (CON) and SL1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Similar to 20% DBP, previous studies in beagle dogs and cats showed that feeding 20% or 5% BSFL also decreased the apparent CP digestibility (Kröger et al, 2020;Do et al, 2022). Moreover, several studies of BSFL in economic animals (Cullere et al, 2016;Hartinger et al, 2021) and cricket meal in beagle dogs (Kilburn et al, 2020) yielded similar results. Thus, we speculate that the reduction in apparent CP and OM digestibility may be related to the 4.65 ~ 6.43% concentration of chitin in the BSFL (Gariglio et al, 2019;Caimi et al, 2020).…”
Section: Discussionmentioning
confidence: 52%
“…Similar to 20% DBP, previous studies in beagle dogs and cats showed that feeding 20% or 5% BSFL also decreased the apparent CP digestibility (Kröger et al, 2020;Do et al, 2022). Moreover, several studies of BSFL in economic animals (Cullere et al, 2016;Hartinger et al, 2021) and cricket meal in beagle dogs (Kilburn et al, 2020) yielded similar results. Thus, we speculate that the reduction in apparent CP and OM digestibility may be related to the 4.65 ~ 6.43% concentration of chitin in the BSFL (Gariglio et al, 2019;Caimi et al, 2020).…”
Section: Discussionmentioning
confidence: 52%
“…Hartinger et al [22] 0, 15%, and 30% of CP from SBM replaced with HI meal. 0, 4%, 10% No differences in intestine morphology parameters.…”
Section: Kim Et Al [19]mentioning
confidence: 99%
“…Despite that fatty acid composition of insect larvae is influenced by the fatty acids in the rearing substrate [ 5 ], the fatty acid composition of TM and HI fat are completely different. While TM fat consists mainly of unsaturated fatty acids (up to 80%), most of which are long-chain fatty acids (LCFA; C18:1 and C18:2; [ 11 ]), the majority of total fatty acids in HI fat are saturated fatty acids (SFA) [ 5 , 16 ]. This explains that HI fat, but not TM fat has a hard consistency at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its high protein content (40%-50% of dry matter (DM) depending on the insect species [5] and provided that the rearing substrate is suitable [6,7]), research dealing with the feed potential of insect biomass has primarily focused on its role as a source of protein. In this context, a large number of studies in different monogastric livestock species demonstrated that insect larvae meal obtained from different edible insect species suitable for large-scale production, such as Tenebrio molitor (TM) and Hermetia illucens (HI), can replace conventional protein sources, like soybean meal, without impairing performance, metabolic health or product quality [8][9][10][11]. Apart from protein, insect larvae contain a significant amount of fat (up to 47% and 43% of DM in HI and TM, respectively, depending on the rearing substrate [12]), which can be obtained by a defatting process during insect meal production in order to increase the protein content and improve the storage stability of the insect meal.…”
Section: Introductionmentioning
confidence: 99%